Analisis Waktu Picking dengan Menggunakan Zone System - Chandra, Agung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
Productivity in order picking time is continuously evaluated and analyzed, because mostly picking is done manually by human. Zone system is one of the methods to increase productivity. In this research, zones is determined by a number of pickers and zone in warehouse is evaluated and divided into 1 zone to 3 zones, congestion and blocking factor are negligible, random storage assignment and S-Shape routing method are used. Total travel time is calculated by summing travel time within storage aisle, travel time in the cross aisle, setup time, and picking time. By comparing among all zones, the result indicates that when the number of zones increases, expected time to finish pick route will be decreased.